Book Reviews. Issue 1 (1st December 2019) - Shivaprakash, H. S.; Tripathy, Manorama; Sreenivasamurthy, J.; Devadevan, Manu V.
Kannada Theatre History 1850–1950: A Sourcebook, K. V. Akshara (ed.), B. R. Venkataramana Aithala and Deepa Ganesh (2018)Manipal: Manipal University Press, 288 pp., ISBN 978-93-82460-84-8, p/bk, Rs. 250Theatre of the Earth – The Works of Heisnam Kanhailal: Essays and Interviews, Heisnam Kanhailal (2016)Calcutta: Seagull Books, 235 pp., ISBN 978-8-17046-353-5, p/bk, Rs. 450Shakespeare: Kannada Spandana (in Kannada), Nataraj Huliyar (ed.) (2016)Bangalore: Kuvempu Bhasha Bharati Pradhikara, 330 pp., ISBN 555-1-23408-868-3, p/bk, Rs. 150Chathirangam (in Malayalam), Ashok D'Cruz (ed.), C. K. Namboothiri (2018)Tirur: Thunchath Ezhuthachan Malayalam University, 256 pp., ISBN 978-8-19374-580-9, h/bk, Rs. 250